Diseño de una metodología de enseñanza para el aprendizaje del estilo crol de la natación en niños de 5 -8 años del Sector 9 de Octubre del Cantón Baba año 2022 - Muñoz Cortez, Erick Alberto (2022)
The present investigation was based on the design of a teaching methodology for learning the front crawl style of swimming in children of 5 - 8 years of age from the 9 de Octubre sector of the Baba canton in 2022. Therefore, a non-specific research design was used. cross-sectional experimental, descriptive-propositive. A swimming style template adapted by the senior swimming coach Jaqueti (2018) was applied to diagnose the learning of the crawl style of swimming to a selected sample of 20 children between 5 - 8 years of age from the 9 de Octubre sector of the Baba canton. In addition, a questionnaire was applied through a survey and interview to measure the need for the design of a methodology to address the problem, supported by theoretical references through documentary research. Through the results of the study, it is expected to design a teaching methodology to contribute to the learning of the crawl style of swimming in children.